1984
DOI: 10.1128/jcm.20.1.133-135.1984
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot analysis of Toxoplasma gondii antigens by human immunoglobulins G, M, and A antibodies at different stages of infection

Abstract: The Toxoplasma gondii antigenic components eliciting the immunoglobulin G (IgG), IgM, and IgA antibody responses were studied by using follow-up sera from a laboratory worker who developed an acute glandular toxoplasmosis after an accidental infection with the protozoa. IgG toxoplasma antibodies reacted with multiple components over a wide molecular weight range from 6,000 to 150,000. In contrast, IgM toxoplasma antibodies reacted predominantly with polypeptides of 6, 25, and 35 kilodaltons, which might be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
2

Year Published

1985
1985
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 9 publications
4
25
0
2
Order By: Relevance
“…Reactivity was observed with polypeptides of 14, 30, 40, and 50 kDa and major reactivity with 25 and 35 kDa. IgA antibodies gave a pattern closely resembling that given by IgM antibodies: only a few antigenic components of 25,35, and 50 kDa as well as polypeptides of 30,32, and 40 kDa (Partanen et al, 1984). At the ultrastructural level, the present data described different localizations of antigens revealed by IgG antibodies that are in agreement with a wide pattern of immunoreactivity observed by Western blot.…”
Section: According Tosupporting
confidence: 87%
See 2 more Smart Citations
“…Reactivity was observed with polypeptides of 14, 30, 40, and 50 kDa and major reactivity with 25 and 35 kDa. IgA antibodies gave a pattern closely resembling that given by IgM antibodies: only a few antigenic components of 25,35, and 50 kDa as well as polypeptides of 30,32, and 40 kDa (Partanen et al, 1984). At the ultrastructural level, the present data described different localizations of antigens revealed by IgG antibodies that are in agreement with a wide pattern of immunoreactivity observed by Western blot.…”
Section: According Tosupporting
confidence: 87%
“…Another low molecular weight component (6 kDa) reacted only with serum from acutely infected individuals. In contrast to the complex antigenic pattern of IgG Toxoplasma antibodies, a very different pattern with only a few antigenic components was obtained in Western blot with IgM Toxoplasma antibodies from sera of patients with acute toxoplasmosis (Partanen et al, 1984). Reactivity was observed with polypeptides of 14, 30, 40, and 50 kDa and major reactivity with 25 and 35 kDa.…”
Section: According Tomentioning
confidence: 76%
See 1 more Smart Citation
“…During the acute phase of toxoplasmosis, we detected IgA antibodies directed against P30 in sera of all patients, sometimes later than specific IgM but always earlier than specific IgG, In the majority of cases, when IgG continued to rise and IgM antibodies persisted ('residual' IgM), IgA antibodies disap- Table 3. Fetuses with anti-P30 IgA antibodies proven to be infected by toxoplasma peared earlier (between 3 and 9 months) and were not detected in the chronic phase of toxoplasmosis, as described in other studies focttsed on the anti-toxoplasma IgA response [4,[8][9][10][11][12][13][14][15][16][17]. We observed only a few exceptions, corresponding to untreated patients, suggesting that the treatment, decreasing the antigenic stimulation, could influence the antibody kinetics.…”
Section: Discussionmentioning
confidence: 79%
“…Although visualization of the tachyzoites in blood, lymph nodes, bone marrow, spleen, brain etc., and of the cyst in brain, muscle and other materials is definitively diagnostic, serologic tests for detecting Toxoplasma-specific antibodies are the primary method for diagnosis (5,19). It is generally believed that IgM antibody specific to T. gondii can be observed in the initial stage of T. gondii infection, while the peak titer of IgG antibody is reached within one to two months of the infection (2,17,18) Recently, Partanen et al (15) reported that IgM Toxoplasma antibodies reacted with a limited number of polypeptides of T. gondii antigen, while IgG Toxoplasma antibodies reacted with multiple components over a wide range of molecular weights (from 6,000 to 150,000). Thus, alteration and expansion of B cell clones reactive to T. gondii may be indicated during the clinical course of acute toxoplasmosis.…”
Section: A Yano Et Almentioning
confidence: 99%